Economic Principles of Predatory (Exclusionary) Pricing in the US and in the EU their (mis)Application in Some Recent Competition Law Cases of the European Community Commission and the Court of First Instance - Bara, Zoltan (Competitio, 2009)
Predatory pricing is one of the most debated issue among the many possibly abusive behaviors of a dominant firm. The general prohibition of the abuse of a dominant power in the competition law is meantto render more difficult to use that power but not to disable them to compete. The borderline between a rough but lawful competitive behavior of a dominant firm and the illegal abuse of the market power could sometimes be very narrow. One of that narrow line is associated with the so called predatory pricing or exclusionary pricing. One of the necessary preconditions for predatory pricing is that the firm is required to set the price below costs. But could it be a sufficient condition as well? Before the AKZO-case lawyers and economists seemed to agree that predatory pricing requires a second phase, after the dominant firm successfully got its prey in the first phase, the recoupment phase during which the dominant firm is able the regain all of his former losses occurred in the first phase. Since the AKZO-case, the Commission succeeded to convince Courts of the EU that it would be enough to make probable but not certain that there had to be a recoupment phase but we don’t have to wait until it really happens. Most of the economists still think that predatory pricing is meaningless without recoupment, and what is more important, it would be beneficial to the consumers during the first phase unless there is no certainty of a second phase.Journal of Economic Literature (JEL) classifications: K21, L12, L41